2014
DOI: 10.1039/c4dt01936a
|View full text |Cite
|
Sign up to set email alerts
|

Ethyleneglycol tungsten complexes of calix[6 and 8]arenes: synthesis, characterization and ROP of ε-caprolactone

Abstract: By varying the reaction conditions, the reaction of [W(eg)3] (eg = 1,2-ethanediolato) with p-tert-butylcalix[n]areneHn (n = 6 or 8) in refluxing toluene affords, following work-up, a number of products which have been fully characterized. From the reaction of p-tert-butylcalix[6]areneH6 with one or two equivalents of [W(eg)3], only the oxo-bridged complex {[W(eg)]2(μ-O)p-tert-butylcalix[6]arene} (1) could be isolated, whereas the use of four equivalents of [W(eg)3], in the presence of molecular sieves, afforde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…4). In one molecule there is a ladder structure, like 4, made up of four Ti(IV) ions and phenolate oxygens (from the L 2 ligand) and bridging oxygens, O(3), O(7), O (9), and O (10). The latter two are oxo dianions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). In one molecule there is a ladder structure, like 4, made up of four Ti(IV) ions and phenolate oxygens (from the L 2 ligand) and bridging oxygens, O(3), O(7), O (9), and O (10). The latter two are oxo dianions.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of tungstocalix [6 and 8]arenes, we observed how different sized calixarene rings and their associated conformations can drastically affect the catalytic activity for the ROP of ε-caprolactone (ε-CL). 10 More recently, McIntosh et al reported preliminary studies on the use of the complex [Ti 4 (L 2 ) (On-Pr) 8 (THF) 2 ] as a catalyst for the ROP of rac-lactide (r-LA) at 130°C. 11 Other titanocalix[n]arene work in this area employs the de-tert-butylated n = 4 system (1,3-di-n-propylcalix[4]arene), with well-behaved ROP of rac-lactide observed when employing either microwave radiation or heat; the former method was beneficial to the rate of polymerization at the expense of control.…”
Section: Introductionmentioning
confidence: 99%
“…10 We have also investigated the use of metallocalix[n]arenes for the ROP of cyclic esters such as ε-caprolactone, and have reported how, for a series of tungstocalix [6 and 8]arenes, different sized rings and their associated conformations can drastically affect the catalytic activity. 11 Molybdo-and tungstocalix [4] arenes were found to be less active. 12 Herein, we have screened several titanocalix [4]arenes, namely [TiCl 2 LIJO) 2 -IJOR) 2 ] (type I: R = Me (1), n-Pr (2) and n-pentyl (3)), the dimeric compound {[TiLIJO) 3 IJOR)] 2 IJμ-Cl) 2 } (R = n-decyl (4)), and [TiIJNCMe)ClIJLIJO) 3 IJOR))]•MeCN (type II, R = Me, 5•MeCN, R = n-propyl 6 and n-pentyl 7) for the ROP of ε-CL, δ-VL and r-LA (the copolymerization of ε-CL and r-LA was also investigated) (Chart 1).…”
Section: Introductionmentioning
confidence: 95%
“…In order to synthesize such bimetallic catalysts, suitable pro-ligand frameworks need to be available, whose coordination chemistry is well suited to binding more than one metal simultaneously in close proximity. Macrocycles are ideal in this respect, and we and others have had some success with the use of calix[n]arenes in ROP [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%